Expression of Urocortin 3 mRNA in the Central Nervous System of the Sea Lamprey Petromyzon marinus - Daniel Sobrido-Cameán; Ramón Anadón; Antón Barreiro-Iglesias (Biology, 2021)
In this study, we analyzed the organization of urocortin 3 (Ucn3)-expressing neuronal populations in the brain of the adult sea lamprey by means of in situ hybridization. We also studied the brain of larval sea lampreys to establish whether this prosocial neuropeptide is expressed differentially in two widely different phases of the sea lamprey life cycle. In adult sea lampreys, Ucn3 transcript expression was observed in neurons of the striatum, prethalamus, nucleus of the medial longitudinal fascicle, torus semicircularis, isthmic reticular formation, interpeduncular nucleus, posterior rhombencephalic reticular formation and nucleus of the solitary tract. Interestingly, in larval sea lampreys, only three regions showed Ucn3 expression, namely the prethalamus, the nucleus of the medial longitudinal fascicle and the posterior rhombencephalic reticular formation. A comparison with distributions of Ucn3 in other vertebrates revealed poor conservation of Ucn3 expression during vertebrate evolution. The large qualitative differences in Ucn3 expression observed between larval and adult phases suggest that the maturation of neuroregulatory circuits in the striatum, torus semicircularis and hindbrain chemosensory systems is closely related to profound life-style changes occurring after the transformation from larval to adult life.